Implementation of Smart Board Visual Media For Autistic Children in Grade 2 Indonesian Language Learning - Hariani Pertiwi; Aswasulasikin Aswasulasikin; Abdul Aziz; Muhammad Husni (Sumber Belajar Sejahtera, 2023)
This study aims to determine how the implementation of visual media